2014
DOI: 10.1111/jgs.12607
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐Year Effects of the Advanced Cognitive Training for Independent and Vital Elderly Cognitive Training Trial on Cognition and Everyday Functioning in Older Adults

Abstract: Objective To determine the effects of cognitive training on cognitive abilities and everyday function over 10 years. Design, Setting, and Participants Ten-year follow-up of a randomized, controlled single-blind trial with 3 intervention groups and a no-contact control group. A volunteer sample of 2832 persons (mean baseline age, 73.6 years; 26% African American) living independently in 6 US cities. Interventions Ten-session training for memory, reasoning, or speed-of-processing.; 4-session booster training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
611
3
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 751 publications
(650 citation statements)
references
References 38 publications
(52 reference statements)
22
611
3
14
Order By: Relevance
“…Of note, three of these studies used a version of InSight and found significant transfer to IADL performance. One of the largest studies of CT to date indicated that far transfer may not be immediately evident, but can emerge over time (Rebok et al 2014). Thus, the lack of significant effects on everyday functional performance in these analyses could be to be examining only immediate posttraining effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, three of these studies used a version of InSight and found significant transfer to IADL performance. One of the largest studies of CT to date indicated that far transfer may not be immediately evident, but can emerge over time (Rebok et al 2014). Thus, the lack of significant effects on everyday functional performance in these analyses could be to be examining only immediate posttraining effects.…”
Section: Discussionmentioning
confidence: 99%
“…Ample evidence demonstrates that CT programs enhance the cognitive abilities targeted by training Edwards et al 2005b;Jaeggi et al 2008;Smith et al 2009). However, there have been mixed findings regarding whether CT generalizes or transfers to untrained tasks Brehmer et al 2012;Rebok et al 2014;Schmiedek et al 2010;Willis et al 2006). Trained tasks refer to the tasks that were employed or directly targeted during the training sessions and are also referred to as primary, proximal, or criterion outcomes (Zelinski 2009).…”
Section: Abstract Aging Cognitive Training Brain Fitness Brain mentioning
confidence: 99%
See 1 more Smart Citation
“…Another found that preschoolers can improve their reasoning skills through practicing computerized tasks involving pattern recognition (Bergman Nutley et al 2011). Older adults who participated in reasoning training maintain their improved reasoning skills for at least 10 years, and scored better on overall health and quality of life measures than a control group (Rebok et al 2014). Fluid reasoning training, in the form of preparing for a reasoning-intensive standardized test, has been linked to increased functional connectivity between the RLPFC and the rest of the fronto-parietal network (Mackey et al 2013), as well as changes in structural connectivity (Mackey et al 2012).…”
Section: Cognitive Trainingmentioning
confidence: 99%
“…The cognitive training program (provided by MindAgilis; London, England) focused on processing speed, executive function, working memory, episodic memory, and mental speed, which are tasks shown to be associated with improved cognitive ability and less difficulty with instrumental activities of daily living. 28,29 All program coaches were certified as personal trainers with mastery of exercise physiology safety and nutritional health practices. Coaches were available via telephone, email, and text messaging.…”
Section: Intervention: Virtual Cognitive Health Programmentioning
confidence: 99%